A review on the humidity reliability of high power white light LEDs. (June 2016) - Singh, Preetpal; Tan, Cher Ming
Abstract: High power white LEDs are replacing current lighting sources, not only for indoor usage, but also for outdoor and harsher environmental applications. This calls for higher reliability with respect to electrical, thermal as well as humidity. In this work, a comprehensive review on the study of humidity reliability of high power LEDs is provided, and the humidity induced degradation mechanisms in packaged high power white LEDs and their failure sites are described. The failure degradation mechanisms are divided into three groups, namely the package level, chip level and interconnect level degradations. Modeling of the moisture degradation is also described, and new test designed for the humidity study is also introduced. The inability of current acceleration model to extrapolate accelerated test results to normal operating conditions for high power LEDs is shown, and this provides a new challenge for the estimation of the lifetime of high power LEDs under normal applications, along with other challenges that need to be addressed. Highlights: Humidity induced degradation studies is significantly lower than the temperature induced degradation studies. The humidity induced degradation mechanisms in each part of a LED is reported. The inability of 85/85 accelerated test and Peck's model are found for the reliability testing of high power LEDs. The future challenges are reported for the humidity reliability of LEDs.